2009
DOI: 10.1177/1403494809347405
|View full text |Cite
|
Sign up to set email alerts
|

Working together — primary care doctors’ and nurses’ attitudes to collaboration

Abstract: DNs were slightly more positive about collaboration than GPs. A positive attitude towards collaboration did not seem to be a part of the GPs' professional role to the same extent as it is for DNs. Professional norms seem to have more influence on attitudes than do gender roles. DNs seem more confident in their profession than GPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 24 publications
8
52
1
2
Order By: Relevance
“…A study among Swedish general practitioners and district nurses also showed similar findings (Hansson, Arvemo, Marklund, Gedda, & Mattsson, 2010). The second hypothesis was based on the postulation that physicians and nurses with higher education levels would be better able to appreciate that holistic management of patients is best achieved by a professional healthcare team that could deal with the bio-psychosocial aspects of patients.…”
Section: Hypothesesmentioning
confidence: 87%
“…A study among Swedish general practitioners and district nurses also showed similar findings (Hansson, Arvemo, Marklund, Gedda, & Mattsson, 2010). The second hypothesis was based on the postulation that physicians and nurses with higher education levels would be better able to appreciate that holistic management of patients is best achieved by a professional healthcare team that could deal with the bio-psychosocial aspects of patients.…”
Section: Hypothesesmentioning
confidence: 87%
“…21 Similar results have been reported by Garber and colleagues, 22 Strechi, 23 Jones and colleagues (comparing anesthesiologist and nurse anesthetists) , 24,25 and by Hansson and colleagues (in a study with Swedish general practitioners and nurses). 26 However, 1 study in Turkey reported more positive attitudes toward collaboration among medical students than among nursing students. 27 It will be interesting to learn whether medical and pharmacy students' attitudes toward collaboration converge as their training proceeds.…”
Section: Discussionmentioning
confidence: 98%
“…17 The principle was likely in operation in several studies of interactions between nurses and physicians. [28][29][30][31][32][33] In the case of students, pharmacy and social work students expressed more positive attitudes toward interprofessional collaboration than did medical students. 34 In one study, however, Turkish medical students demonstrated a more positive attitude toward collaboration than did nursing students.…”
Section: Discussionmentioning
confidence: 99%